Managing Diverse R&D Teams toward Creative Performance, Qualitative Research - Yazdi, Hannaneh (My University, 2016)
Due to increasing globalization, teamwork diversity is increased and organization’s environ-ment is changing. Additionally, organizations are hardly competing with each other since, tech-nology is developing so fast and the market products and services have been gotten various based on costumers’ demands every day. Necessity of applying a wide variety of skills within the companies brings this requirement to bring diverse team members in same teamwork. There-fore, managers need to understand the value of the diversity, which can influence on creative teamwork’s performance, then the result and outcome is organization’s goals. Also mangers need to learn concept of diversity in workforce and be aware of diversity’s aspects in teamwork environment. Diversity has benefits and disadvantages, which can effect on team performance. Managers need to understand these positive and negative sides of diversity and then start to control the negative side and conduct diverse teams to positive side. Afterward, they can increase creative performance within diverse teams based on organization’s goals. This study is a qualitative research by using semi-structured interviews as data collection methods. The main aim of this study is managing diversity R&D teams toward creative perfor-mance by avoiding the negative side of the diversity and increasing the diversity’s value and benefits based on organization’s goals.
Keywords: Samhällsbyggnadsteknik; Civil Engineering